Ответы и объяснения

Лучший Ответ!
2012-04-15T05:07:28+04:00

 -2     -2
a   - b                     ab                           
___________  : __________= 1/ab

  -4     -4             -2      -2 

a    - b               a    + b



1) 1/а^2-1/в^2=(а^2-в^2)/а^2*в^2

2) 1/а^4-1/в^4=(a^4-в^4)/a^4*b^4

3)  ((а^2-в^2)/а^2*в^2):((a^2-в^2)(a^2+в^2)/a^4*b^4)=((а^2-в^2)/(а^2*в^2))*((a^4*b^4)/(a^2-в^2)(a^2+в^2))= (a^2*b^2)/a^2+b^2

4) 1/a^2+1/b^2=(a^2+b^2)/a^2*b^2

5) ab:(a^2+b^2)/a^2*b^2=  ab *a^2*b^2/a^2+b^2=a^3*b^3/a^2+b^2

6) ((a^2*b^2)/a^2+b^2):(a^3*b^3/a^2+b^2)= ((а^2*b^2)*a^2+b^2)/((a^2+b^2)*a^3*b^3)=1/ab